Glycemic Status and its Effect in Neonatal Sepsis in a Tertiary Care Hospital (Bangladesh Journal of Child Health, 2017)
Introduction: Neonatal sepsis can alter the glucose level and both hypoglycemia and hyperglycemia may occur. A high or low blood glucose level may have a significant effect on the outcomes in patients of neonatal sepsis.Objective: To see the glycemic status and its effect on outcome of neonatal sepsis.Methods: This prospective observational study was done in the department of paediatrics, Sylhet MAG Osmani Medical College Hospital, Sylhet from July 2013 to December 2013. Clinically suspected neonatal sepsis cases were enrolled in the study. Venous blood was collected before giving any intravenous fluid or antibiotics for blood sugar, full blood counts, CRP levels and blood culture and send to labouratory within half hour of collection. All patients included in this study were treated accordingly and followed up strictly. Blood glucose level and mortality of neonates having hypoglycemia and hyperglycemia were analyzed among CRP and culture positive patients. Quantitative data were expressed as mean and standard deviation. Qualitative data were expressed as frequency and percentage and comparison carried by Chisquare (÷2) test.Results: A total of 62 patients clinically diagnosed as neonatal sepsis were studied. Fifty two (83.9%) patients were found CRP positive and 21(33.9%) patients were blood culture positive. Glycemic status was analyzed among CRP and culture positive patients. Majority (71.2%) patients were found normoglycemic, 13.5% were found hypoglycemic and 15.3% were found hyperglycemic in this study. Fifty one (82.2%) patients were cured and 9(17.8%) were died. Mortality was high in hypoglycaemic patients (42.8%) compare with normoglycaemic patients (10.8%), but the difference was not statistically significant (p>0.05) between two groups whereas mortality was also high in hyperglycaemic patients (50%) compare with normoglycaemic patients (10.8%) and the difference was statistically significant (p